Women resisting violence : spirituality for life (Manila : Institute of Women's Studies, 1996)
Proceedings of a conference held Dec. 7-12, 1994 in San Jose, Costa Rica
Includes bibliographic references
Keywords: Women -- Social conditions -- Congresses; Women -- Crimes against -- Congresses; Sex discrimination against women -- Congresses; Feminist theory -- Congresses; Liberation theology -- Congresses